Analyse von PDE-DAE-Systemen mittels einer Normalform - Mohr, Andreas; Deutscher, Joachim (Methoden und Anwendung der Regelungstechnik, 2013)

Parametric state feedback design for linear infinite-dimensional systems - Mohr, Andreas; Deutscher, Joachim (12th European Control Conference 2013, 2013)
In this paper, a parametric approach for state feedback controllers for a class of linear infinite-dimensional systems is presented. Therein, besides the closed-loop eigenvalues, the corresponding parameter vectors are introduced as design parameters. This allows not only to assign finitely many eigenvalues, but also the corresponding eigenvectors. The presented approach is applied to solve a partial eigenstructure assignment problem for linear time-delay systems with point-delays. An example for the usefulness of the proposed design method is then given by a partial input-output decoupling of a simple time-delay system. © 2013 EUC